GLINT: GlucoCEST in neoplastic tumors at 3 T-clinical results of GlucoCEST in gliomas - Bender, Benjamin; Herz, Kai; Deshmane, Anagha; Richter, Vivien; Tabatabai, Ghazaleh; Schittenhelm, Jens; Skardelly, Marco; Scheffler, Klaus; Ernemann, Ulrike; Kim, Mina; Golay, Xavier; Zaiss, Moritz; et al. (Magnetic Resonance Materials in Physics Biology and Medicine, 2021)
Objective Clinical relevance of dynamic glucose enhanced (DGE) chemical exchange saturation transfer (CEST) imaging has mostly been demonstrated at ultra-high field (UHF) due to low effect size. Results of a cohort study at clinical field strength are shown herein. Materials and methods Motion and field inhomogeneity corrected T1.-based DGE (DGE.) images were acquired before, during and after a d-glucose injection with 6.3 s temporal resolution to detect accumulation in the brain. Six glioma patients with clear blood-brain barrier (BBB) leakage, two glioma patients with suspected BBB leakage, and three glioma patients without BBB leakage were scanned at 3 T. Results In high-grade gliomas with BBB leakage, d-glucose uptake could be detected in the gadolinium (Gd) enhancing region as well as in the tumor necrosis with a maximum increase of.DGE. around 0.25%, whereas unaffected white matter did not show any significant DGE. increase. Glioma patients without Gd enhancement showed no detectable DGE. effect within the tumor. Conclusion First application of DGE. in a patient cohort shows an association between BBB leakage and DGE signal irrespective of the tumor grade. This indicates that glucoCEST corresponds more to the disruptions of BBB with Gd uptake than to the molecular tumor profile or tumor grading.
CRIS-Team WoS Importer:2021-12-24